Syphilis Vaccine Development: Requirements, Challenges and Opportunities - Cameron, Caroline E. (Sex Transm Dis, 2018)
Syphilis, caused by the spirochete Treponema pallidum subspecies pallidum, continues to be a prevalent disease in low- and middle-income countries, and has re-emerged in key populations, including men who have sex with men, in high-income nations. The rising number of cases shows syphilis elimination will require augmentation of public health screening and treatment campaigns with syphilis vaccine development and implementation initiatives. Optimal vaccine candidates, deciphered from careful consideration of the pathogenic mechanisms employed by T. pallidum, will need to be paired with appropriate human-track adjuvants designed to elicit the correlates of protection needed to prevent infection/disease. This article provides an overview of the development pipeline customized for a syphilis vaccine, including the preferred product characteristics, the investment case, and a proposed vaccinogen selection strategy outlining the essential qualities that need to be targeted by a syphilis vaccine.